VALUASI: NILAI SEBENARNYA VS NILAI TAK SEBENARNYA - Dr. Said kelana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2011)
The purpose of valuation is to find the intrinsic value of assets. It is performed by estimating the future value. There are a number of assumption required and methods applied for valuation. Consecuently, there are a wide range of value resulted by some valuation. That is difficult to find the true value of valuation. Keywords: valuation, intrinsic value, discount model, relative model.